Concordance between site of onset and limb dominance in amyotrophic lateral sclerosis. Issue 8 (18th June 2010) - Turner, M R; Wicks, P; Brownstein, C A; Massagli, M P; Toronjo, M; Talbot, K; Al-Chalabi, A
Abstract : Background: Focality of onset of amyotrophic lateral sclerosis (ALS) is not understood. Attempts to implicate physical exercise in the aetiology of ALS have provided inconsistent results. If physical use of a limb were important in defining the site of onset, then handedness might be expected to influence the side of upper limb-onset disease and footedness likewise in lower limb-onset ALS. Methods: ALS patients registered with an internet-based support site were invited to complete an online questionnaire concerning site of onset of symptoms and their dominant hand and foot. A binomial test of proportions was used to investigate the null hypothesis that handedness and footedness do not influence side of onset in upper and lower limb-onset ALS, respectively. Results: 343 ALS patients with limb-onset disease were studied. For upper limb-onset patients, there was concordance for side of onset and handedness (64%; p<0.0006). For lower limb-onset patients, concordance for side of onset and footedness was absent. The frequency of left handedness was commensurate with that found in the general population. Interpretation: These results are potentially consistent with the hypothesis that exercise influences pathogenesis in ALS since routine physical demands on the upper limb are heavily influenced by limb dominance, whereas in the lower limbs the commonest function is standing or locomotion, which uses both legs equally. However, there may also be an inherent cortical vulnerability underlying upper limb-onset laterality, possibly influenced by changes in neuronal connectivity and cortical excitability in relation to handedness and reflected by the "split hand" phenomenon consistently observed in ALS.